A dosimetry measurement on head and neck sensitive organs during CT scan, a comprehensive study - Khoshhal, Amir Reza; Torshabi, Ahmad Esmaili; Zehtabian, Mehdi (Applied radiation and isotopes, 2025)
The increasing use of Computed Tomography (CT) significantly aids in diagnosing various diseases. However, patient radiation exposure remains a major concern. This study presents experimental dosimetry measurements of the radiation dose received by sensitive organs in the head and neck region during CT imaging with a Canon CT scanner using scan parameters of 135 kV, 150 mA, 6.6 s, and 5 mm slice thickness. Calibrated GR-200 Thermoluminescent Dosimeters (TLDs) were used to measure the absorbed doses at various points on a Rando phantom. A total of 84 TLDs were used for: the occipital (24) and temporal lobes (24), the thalamus (12), the hypothalamus (6), right parotid gland (4), eyes (4) and for background dose measurement (10). The absorbed doses were found to be 23.84 mGy for the occipital lobe, 23.11 mGy for the temporal lobe, 22.81 mGy for the hypothalamus, 22.94 mGy for the thalamus, 17.63 mGy for the left eye, 17.08 mGy for the right eye, and 28.08 mGy for the right parotid gland. The highest and lowest doses were observed in the right parotid gland and eyes, respectively. This study provides valuable insights for clinicians and radiologists, understanding the risk of overexposure with a quantitative vision in sensitive head and neck organs during scanning especially in pediatric and repeat-scan cases. •Absorbed dose measurement at sensitive organs during Head and Neck CT scan.•Absorbed dose assessment at eyes, occipital, temporal, thalamus, hypothalamus and parotid in a comparative fashion.•Using TLDs dosimeters inside Anthropomorphic Rando Phantom for dose measurement.•Quantifying the amount of imaging dose reached to the organs during CT considering the risk of side effects.